Solidaritas Masyarakat dalam Penghijauan Pesisir di Desa Bima Karya Kecamatan Bualemo - Mohammad Bayu Irawan; Eka Reza Saputra Widodo; Yusfriandi Dwi Ariesna; Suryadi Syamsuddin; Marini Susanti Hamidun; Iswan Dunggio (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research focuses on how community solidarity in Bimakarya Village, Bualemo Sub-district, contributes to the success of the coastal reforestation programme and its impact on social-ecological life. The method used in writing is by using a qualitative approach. Data collection techniques using observation and interview data. The result of the findings of this research writing is that community solidarity in coastal reforestation in Bimakarya Village, Bualemo Subdistrict is not only a physical activity, but is one of the processes in preserving the environment and building community awareness and concern for the coastal environment.